The wicked heir ebook - Michels, Elizabeth (Spare Heirs, 2017)
"Historical romance devotees will enjoy Michels's adoring use of some of the classic tropes of the genre—the spare heir, the wrong brother as hero, the heroine in men's clothing—but what makes the book so enjoyable is the way Michels makes the familiar fresh."— SARAH MACLEAN , The Washington Post for The Infamous Heir The Spare Heirs Society Cordially Invites You to Meet Fallon St. James: The Mastermind When the love of Lady Isabelle Fairlyn's life is betrothed to her twin sister, Isabelle vows to find a suitable replacement before the end of the season. He must be a talented dancer, have a keen fashion sense, and be perfectly dashing in every way. Fallon St. James is the farthest thing from perfectly anything. As head of the secretive Spare Heirs Society, he must stick to the shadows...even as Isabelle's friendship pulls him reluctantly into the light. But when Isabelle gets involved with the one man who could destroy Spares, Fallon must decide between protecting his life's work—or risking everything to save the woman whose warm smile leaves him breathless. Praise for Elizabeth Michels: "Michels's latest is the complete package: a captivating romance with gripping suspense wrapped up in a novel to be savored."—Publishers Weekly STARRED REVIEW for The Infamous Heir "Playing with the themes of deception and authenticity, this romance delightfully emulates a Jane Austen-ish comedy of manners."—Kirkus Reviews for The Rebel Heir "Rich with wit and charm."—Publishers Weekly for How to Lose a Lord in 10 Days or Less "Michels' fresh and funny debut will delight readers with its endearing characters and infectious mix of sweet yet sexy romance and realistic yet wry wit."—Booklist Online STARRED REVIEW for Must Love Dukes